(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the knowledge of stroke prevention among patients with hypertension at Ha Dong General Hospital in 2024–2025. Methods: A cross-sectional study was conducted. Results: The study was carried out on 238 patients receiving treatment for hypertension at Ha Dong General Hospital. A structured questionnaire was used to assess patients’ knowledge of stroke prevention. The findings showed that 60.5% of hypertensive patients had adequate knowledge of stroke prevention, while 39.5% had inadequate knowledge of stroke prevention. Conclusion: The proportion of hypertensive patients with inadequate knowledge of stroke prevention remains high. Therefore, active measures are needed to enhance communication and improve knowledge of stroke prevention among patients with hypertension.